2018
DOI: 10.18502/kss.v3i10.3135
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Industry Internship, Career Guidance, and Working World Information to the Students Work Readiness of Grade XI SMK Palebon Semarang in Academic Year 2017/2018

Abstract: The aim of Vocational High School is to prepare students to be ready in entering working world. The objective of this study is to examine the influences of Industry Internship, career guidance, and working world information to the work readiness.The population of this research is students of Grade XI SMK Palebon Semarang.The total population of this research is 237 students from 6 classes with 149 students as the sample calculated by Slovin formula with 5% error rate. The data collection techniques use observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…This industrial work practice is very beneficial for students because they can read how the situation is in the workplace, besides that those who graduate in industrial work practice will have opportunities to become employees later. In line with research (Purnama et al, 2018), simultaneously, industrial work practices, career guidance, and information on the world of work have a positive and significant effect on student work readiness by 46.6%. In line with research conducted by (Liyasari & Suryani, 2022), research shows industrial work practices have a positive and significant effect on work readiness of 4.49%.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…This industrial work practice is very beneficial for students because they can read how the situation is in the workplace, besides that those who graduate in industrial work practice will have opportunities to become employees later. In line with research (Purnama et al, 2018), simultaneously, industrial work practices, career guidance, and information on the world of work have a positive and significant effect on student work readiness by 46.6%. In line with research conducted by (Liyasari & Suryani, 2022), research shows industrial work practices have a positive and significant effect on work readiness of 4.49%.…”
supporting
confidence: 56%
“…In line with the factors that affect work readiness, namely emotional intelligence and positive influence (Sabilah, J., Riyanti. S.N & Saputra, N, 2021), then industrial work practices have a positive effect on student work readiness (Purnama et al, 2018), soft skills also have a positive effect on student work readiness (Fatimah, D., Trisnaningsih, T. & Pujiati. P., 2022) and self-efficacy have a positive effect on student work readiness (Syofyan, 2022).…”
Section: The Influence Of Emotional Intelligence Industrial Work Prac...mentioning
confidence: 99%
“…In particular, the alignment of academic knowledge with real-world applications was highlighted as a key contributor to improved employability. Several studies have consistently shown that practical experience gained through programs like SWA positively influences students' readiness for the workplace [65,66]. The integration of work seems to develop a deeper understanding of their field and apply theoretical knowledge in real-world scenarios.…”
Section: Discussionmentioning
confidence: 99%